Evidence that cultural groups differ in their abilities to detect fake accents: a follow up - Jonathan R. Goodman; Robert A. Foley (Evolutionary Human Sciences)
We recently reported that cultural group membership may be a predictor of the likelihood that an individual will detect a faked accent in a recording. Here, we present follow-up data to our original study using a larger data set comprised of responses from the across the world. Our findings are in line with our previous work and suggest that native listeners perform better at this task than do non-native listeners overall, although with some between-group variation. We discuss our findings within the context of signals of trustworthiness and suggest future avenues of research.